2021
DOI: 10.52547/iem.7.1.45
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Tissue Distribution of Ornithobac-terium rhinotracheale in different Organs of Turkeys

Abstract: Background: This study was designed to investigate the frequency and tissue distribution of Ornithobacterium rhinotracheale (ORT) in turkeys with respiratory syndrome in Isfahan province.Materials & Methods: Totally, samples were taken from the trachea, lung, air sac, infraorbital sinus, hock joint, blood of heart, brain, liver, spleen, intestine, and kidney of 30 turkey flocks. After DNA extraction, a 787 bp fragment of 16S rRNA gene of ORT was amplified. Findings: The PCR results revealed that 53% of turkeys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…PCR results showed that 53% of the turkeys were infected with ORT. Moreover, their study showed that although ORT is found mainly in the respiratory tract, it can be systemic and infect some other organs, including the joints, brain, liver, spleen and heart blood, but it cannot affect the intestines and kidneys (Karimi-Dehkordi et al, 2021). Mirzaie and Hassanzadeh (2013) reported the prevalence of Ornithobacterium by PCR in turkeys, partridges, quails and pigeons.…”
Section: Discussionmentioning
confidence: 99%
“…PCR results showed that 53% of the turkeys were infected with ORT. Moreover, their study showed that although ORT is found mainly in the respiratory tract, it can be systemic and infect some other organs, including the joints, brain, liver, spleen and heart blood, but it cannot affect the intestines and kidneys (Karimi-Dehkordi et al, 2021). Mirzaie and Hassanzadeh (2013) reported the prevalence of Ornithobacterium by PCR in turkeys, partridges, quails and pigeons.…”
Section: Discussionmentioning
confidence: 99%